2019
DOI: 10.3390/toxins11040217
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Toxic Effects of Ochratoxin A in Human Embryonic Stem Cells

Abstract: Ochratoxin A (OTA) is a mycotoxin produced by different Aspergillus and Penicillium species, and it is considered a common contaminant in food and animal feed worldwide. On the other hand, human embryonic stem cells (hESCs) have been suggested as a valuable model for evaluating drug embryotoxicity. In this study, we have evaluated potentially toxic effects of OTA in hESCs. By using in vitro culture techniques, specific cellular markers, and molecular biology procedures, we found that OTA produces mild cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…There are some data on mycotoxicoses in children, infants, and even in embryonic stage, but these topics definitely need additional attention from the scientific community. Using human embryonic stem cells (hESCs), a research group showed the dose dependency of OTA toxicity (Erceg et al, 2019). More data could give us a clearer view on how different mycotoxin exposures affect the differentiation of hESC cells.…”
Section: The Risks Of Mycotoxins At Different Stages Of Lifementioning
confidence: 99%
“…There are some data on mycotoxicoses in children, infants, and even in embryonic stage, but these topics definitely need additional attention from the scientific community. Using human embryonic stem cells (hESCs), a research group showed the dose dependency of OTA toxicity (Erceg et al, 2019). More data could give us a clearer view on how different mycotoxin exposures affect the differentiation of hESC cells.…”
Section: The Risks Of Mycotoxins At Different Stages Of Lifementioning
confidence: 99%
“…OTA-contaminated foods, especially plant foods, were related to the occurrence of many diseases in animals and humans, and it was a potential health threat with nephrotoxicity, hepatotoxicity, teratogenicity, immunotoxicity and neurotoxicity [ 43 ]. More and more research results indicated that even a very low level of OTA intake will accumulate in the human body [ 44 , 45 ]. The acute toxicity of OTA showed wide variability, which is related to animal sex, species and sample size.…”
Section: Occurrence Contamination and Toxicity Of Mycotoxinsmentioning
confidence: 99%
“…Because of its thermal stability, it can also be found in heat‐treated food products (Gambacorta et al., 2018). OTA has been shown to have pathogenesis of various forms of human nephropathies such as kidney cancer (Erceg et al., 2019). Therefore, because of the side effects of this toxin on human health and the economic losses caused by food products contamination, it is essential to reduce the risk of contact to this compound, typically during preventive assesses including proper treatment of plant products through pre‐harvest, harvest, and post‐harvest.…”
Section: Introductionmentioning
confidence: 99%